PENERAPAN MODEL ROLE PLAYING TERHADAP MOTIVASI BELAJAR SEJARAH KELAS XI MIA SMAN 9 PONTIANAK - Karneti Karneti; Agus Sastrawan Noor; Ika Rahmatika Chalimi (Universitas Tanjungpura, 2020)
AbstractThis research aimed to find out the effect of role playing learning models on students' learning motivations in the history subjects of class XI MIA SMAN 9 Pontianak. The research used kuantitaitif experiment type one group pretest-posttest designs. This determination of samples used purposive sampling. The research instruments used pre-test and post-test questionnaires. The results of this research showed; The results of the pre-test score 60.47% with sufficiently categorized. The results of the post-test score 78% with strongly categorized. Based on r square score shows the contribution of role playing learning model influence to learn motivation of students is 32.8%, remaining influenced by other variables. Hypothesis test results showed that t count by 4,078 greater > from table t 2,032. So it can be drawn conclusions that Ho rejected and Ha accepted, which means there was an influence of role playing learning model on the motivation of learning students on the history subjects of grade XI MIA 3 SMAN 9 Pontianak. Keywords: History Subject, Motivational Learning, Role Playing.